THE EFFECT OF COMPANY SIZE, SOLVENCY AND AUDIT COMMITTEE ON DELAY AUDIT - Muhammad Rizal Saragih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Delay in financial reporting, a company complaint. Because the investor no longer believes. Therefore, audit delay needs to be addressed. This study aims to analyze and describe audit delay factors. The research method used is quantitative with secondary data. The populations in this study were all manufacturing companies listed on the Indonesia Stock Exchange. The sample technique used is purposive with the criteria specified are companies those publish audited financial statements for four consecutive years and use the rupiah currency, so the total number of samples in this study is 100 data. Independent variables in this study are company size, solvability and audit committee, variables dependent in this study is audit delay. The data analysis technique used is multiple linear regressions. The results of the analysis show that the solvability variable has a significant effect on audit delay. While the variable size of the company and the audit committee does not have a significant effect on audit delay